2023
DOI: 10.1177/1098612x221148565
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypersomatotropism and hyperthyroidism in cats with diabetes mellitus from referral centers in Buenos Aires (2020–2022)

Abstract: Objectives The aim of this study was to estimate the prevalence of hypersomatotropism (HST) and hyperthyroidism in cats with diabetes mellitus (DM) from referral centers in Buenos Aires, Argentina. Methods This was a prospective study. Systematic screening of serum insulin-like growth factor 1 (IGF-1) and total thyroxine was performed in all cats diagnosed with DM at referral centers in Buenos Aires between February 2020 and February 2022. Results In total, 154 diabetic cats were evaluated (99 males and 55 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Studies in Argentina, mainland Europe and the UK have reported a 15-25% prevalance of concurrent HST among feline diabetic patients. 9 , 22 , 23 Weight gain with poorly controlled diabetes mellitus occurs in roughly 17% of cats with HST, while 42% experience weight loss. 24 The clinical characteristics of 133 cats with a diagnosis of HST are presented in Table 1 .…”
Section: Presenting Signs and Diagnostic Testingmentioning
confidence: 99%
“…Studies in Argentina, mainland Europe and the UK have reported a 15-25% prevalance of concurrent HST among feline diabetic patients. 9 , 22 , 23 Weight gain with poorly controlled diabetes mellitus occurs in roughly 17% of cats with HST, while 42% experience weight loss. 24 The clinical characteristics of 133 cats with a diagnosis of HST are presented in Table 1 .…”
Section: Presenting Signs and Diagnostic Testingmentioning
confidence: 99%